Ensuring an Essential Supply of Allied Health Professions (AHP) Placements: Using Crowdsourcing to Develop a National Call to Action - St. John-Matthews, Janice; Hobbs, Charlotte; Chapman, Paul; Marsden, David; Allarton, Ruth; Booth, Austin; Martin, Fiona; Woodley, Julie; Harden, Beverley (International Journal of Practice-based Learning in Health and Social Care, 2021)
Sustainable growth in the Allied Health Professions (AHP) workforce is an ambition of the United Kingdom’s NHS Long Term Plan. However historically, access to good quality placements has been a barrier to increasing pre-registration training numbers. This article focuses on work carried out by Health Education England (HEE) to gain insights on the impact of the COVID-19 pandemic on capacity. Using a pragmatic, embedded mixed-methods approach, insights were gathered using an online workshop, crowdsourcing, open for two weeks in the summer of 2020. AHP placement stakeholders could vote, share ideas or comment. Descriptive data were extracted, and comments made were analysed using inductive thematic analysis. Participants (N = 1,800) made over 8,500 comments. The themes identified included: diversity of placement opportunity, improved placement coordination, a more joined-up system, supervision models and educator capacity. Alongside considering the challenges to placement capacity, several areas of innovative practice owing to the pandemic were highlighted. Generated insights have shaped the aims and objectives of the Health Education (HEE) pre-registration AHP student practice learning programme for 2020/2021 and beyond. The COVID-19 pandemic has disrupted the delivery of AHP placements. In the absence of face-to-face activities, crowdsourcing provided an online data collection tool offering stakeholders an opportunity to engage with the placement capacity agenda and share learning. Findings have shaped the HEE approach to short-term placement recovery and long-term growth.